Hydrogeochemical controls on arsenic mobility in an arid inland basin, Southeast of Iran: The role of alkaline conditions and salt water intrusion. (June 2019) - Dehbandi, Reza; Abbasnejad, Ahmad; Karimi, Zohreh; Herath, Indika; Bundschuh, Jochen
Abstract: Elevated inorganic arsenic concentrations in groundwater has become a major public and environmental health concern in different parts of the world. Currently, As-contaminated groundwater issue in many countries and regions is a major topic for publications at global level. However, there are many regions worldwide where the problem has still not been resolved or fully understood due to inadequate hydrogeochemical investigations. Hence, this study evaluates for the first time the hydrogeochemical behavior of the arid and previously unexplored inland basin of Sirjan Plain, south east (SE) Iran, in order to assess the controlling factors which influence arsenic (As) mobility and its distribution through groundwater resources. Total inorganic arsenic concentration was measured using inductive-coupled plasma optical emission spectrometry (ICP-OES). Arsenic content in groundwater of this region ranged between 2.4 and 545.8 μg/L (mean value: 86.6 μg/L) and 50% of the samples exceeded the World Health Organization (WHO) guideline value of 10 μg/L in drinking water. Groundwater was mainly of Na-Cl type and alkaline due to silicate weathering, ion exchange and evaporation in arid conditions. Elevated As concentrations were generally observed under weakly alkaline to alkaline conditions (pH > 7.4). Multivariate statistical analysis including cluster analysis and bi-plot grouped As with pH and HCO3 and demonstrated that the secondary minerals including oxyhydroxides of Fe are the main source of As in groundwater in this region. The desorption of As from these mineral phases occurs under alkaline conditions in oxidizing arid environments thereby leading to high levels of As in groundwater. Moreover, evaporation, ion exchange and saltwater intrusion were the secondary processes accelerating As release and its mobility in groundwater. Based on the results of this study, desorption of As from metal oxy-hydroxides surfaces under alkaline conditions, evaporation and intrusion of As-rich saline water are considered to be the major factors causing As enrichment in arid inland basins such as those in southeast Iran. This study proposes the regular monitoring and proper groundwater management practices to mitigate high levels of arsenic in groundwater and related drinking water wells of Sirjan Plain. Graphical abstract: Image 1 Highlights: This study reveals geogenic As of groundwater in previously unexplored Sirjan plain, Iran. 50% of groundwater samples exceed the drinking water guideline value for As. Groundwater is predominantly of Na-Cl type and alkaline nature. Oxyhydroxides of Fe are the main sources of As in groundwater. Evaporation, ion exchange and saltwater intrusion processes enhance As mobility.